Pengaruh kualitas produk dan citra merek terhadap keputusan pembelian buku di store intrans publishing Malang - Junaris, Imam; Haryanti, Nik (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2024)
The purpose of this study is to determine the influence of product quality and brand image on book purchase decisions at Store Instrans Publishing Malang. The research method used is a quantitative research approach. The sample in this study was 100 consumers. With sampling techniques using purposive sampling, which is a sampling technique with certain considerations. Data analysis using multiple regression tests. The results of his research showed that product quality affects book purchase decisions at Instrans Publishing Store Malang. This means that the higher the quality of the product, the higher the purchase decision. Brand image influences book purchase decisions at Instrans Publishing Store Malang. This means that the higher the brand image, the higher the purchase decision.